2019
DOI: 10.1016/j.scitotenv.2018.11.325
|View full text |Cite
|
Sign up to set email alerts
|

Viability-based quantification of antibiotic resistance genes and human fecal markers in wastewater effluent and receiving waters

Abstract: Antibiotic resistance is a public health issue with links to environmental sources of antibiotic resistance genes (ARGs). ARGs from nonviable sources may pose a hazard given the potential for transformation whereas ARGs in viable sources may proliferate during host growth or conjugation. In this study, ARGs in the effluent from three municipal wastewater treatment plants (WWTPs) and the receiving surface waters were investigated using a viability-based qPCR technique (vPCR) with propidium monoazide (PMA). ARGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…sul 1 was the most commonly detected ARG transcript in the sewer samples. This has consistently been reported as the most abundant ARG among all matrices in sewer system (wastewater [ 3 5 , 7 , 32 ], sewer sediment [ 2 , 5 ], and biofilms [ 2 , 7 ]) including in the paired DNA samples for this study ranging from − 1 to − 2 Log10 copies per copy of 16S rRNA gene [ 5 ]. tet (G) and bla TEM have also been commonly detected in sewer bacterial communities [ 2 5 , 7 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…sul 1 was the most commonly detected ARG transcript in the sewer samples. This has consistently been reported as the most abundant ARG among all matrices in sewer system (wastewater [ 3 5 , 7 , 32 ], sewer sediment [ 2 , 5 ], and biofilms [ 2 , 7 ]) including in the paired DNA samples for this study ranging from − 1 to − 2 Log10 copies per copy of 16S rRNA gene [ 5 ]. tet (G) and bla TEM have also been commonly detected in sewer bacterial communities [ 2 5 , 7 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 73%
“…A previous study on soil samples from alpine forests, alpine tundra, grasslands, and wetlands showed that in some soil ecosystems, extracellular DNA and DNA from dead cells can inflate the prokaryotic community richness and misestimate the relative abundances of bacterial taxa [ 47 ]. Another study in chlorinated wastewater effluent showed an average ratio of ~ 0.3 of 16S rRNA genes from viable cells to 16S rRNA genes from dead cells and extracellular DNA [ 3 ]; this is expected to be higher in untreated wastewater influent. This could explain why more sequences of some of the relevant taxa containing human pathogens were detected in the rRNA gene microbiome than in the rRNA transcript microbiomes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ARG quantification, amplificationdependent methods such as quantitative PCR (qPCR), high-throughput qPCR (HT-qPCR) and digital PCR (dPCR) are particularly useful, in part due to their ease of execution, robustness, specificity and sensitivity. qPCR can provide information on the abundance of the targeted ARGs in different genetic contexts including viable bacteria, mobile DNA fragments like MGEs and "free" environmental DNA (extracellular DNA), depending on the DNA extraction technique(Dong et al, 2019;Eramo et al, 2019). For example, propidium monoazide can be used to remove DNA from dead cells and extracellular DNA in the sample during the extraction process, thus allowing for the obtainment of DNA from live cells only(Wagner et al, 2008).Similarly, it may also be possible to selectively target plasmids and separate them from chromosomal DNA.…”
mentioning
confidence: 99%
“…When used in conjunction with a DNA-binding dye, such as propidium monoazide (PMA), extracellular and non-viable cell DNA are covalently cross-linked by the dye and hindered from detection in the downstream PCR and sequencing processes, allowing the detection of the viable microbes in specific (Kibbee and Örmeci, 2017 ). With more studies unraveling the possible interferences and optimizing the procedures of PMA treatment, the use of PMA in complex environmental sample matrices, such as sewage, has become more common in the past decade (Li et al, 2014b ; Eramo et al, 2019 ). Applications of PMA-coupled qPCR or sequencing have discovered a great variety of viable cells in disinfected effluents (Pang et al, 2016 ; Kibbee and Örmeci, 2017 ).…”
Section: Introductionmentioning
confidence: 99%